Polymorphism of the renin-angiotensin system genes and endothelial NO-synthase gene in obese patients with arterial hypertension - Ashcheulova, T.V.; Gerasimchuk, N.N.; Demydenko, G.V.; Kulikova, M.V. (Вiopolymers and Cell, 2018)
The review is dedicated to relationships between the blood pressure and body mass. Endothelial dysfunction and imbalance of neurohumoral systems, namely, the pathological increase in the activity of the renin-angiotensin system, in combination with obesity are the main mechanisms of the of the hypertonic disease pathogenesis. Here we discuss the research on polymorphism of the renin angiotensinic system genes and the endothelial synthase nitric oxide gene. The difficulty lies in the correct assessment of associations of alleles which have clinical significance. It is essential to determine precisely the associations of gene polymorphisms in the hypertonic disease with obesity. This provides an opportunity to identify new personified approaches to the treatment of patients with this complex pathology. Keywordsendothelial nitric oxide synthase, renin-angiotensin system, gene polymorphism, hypertonic disease, obesity